In vitro somatic embryos multiplication of Eurycoma longifolia Jack using Temporary Immersion System RITA® - Noor Madihah Mohd,; Hafsah Ja'afar,; Dhiya Dalila Zawawi,; Nadiawati Alias, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Temporary immersion system, Recipient for Automated Temporary Immersion® (RITA®), is one of the innovative systems that allow the production of large number of somatic embryos or plantlets via in vitro plant propagation. It has been widely used to avoid associated problems such as low multiplication rate of somatic embryos and hyperhydricity during plant propagation. Thus, an attempt was made to investigate optimal parameters such as immersion time and immersion frequency, for the multiplication of direct somatic embryogenesis from cotyledon culture of Eurycoma longifolia Jack using RITA®. Four periods of immersion time (1, 5, 10 and 15 min every 4 h) were evaluated for the efficiency in somatic embryos multiplication. In order to optimize repetitive somatic embryogenesis, three different immersion frequencies (5 min immersion every 2, 4 and 8 h) were applied. The highest number of secondary embryos (69.67 ± 9.73) was found significant when immersing the globular, primary embryos for 5 min every 4 h as compared to other immersion time tested. The secondary somatic embryos obtained in this study could be further used for the development of plantlet regeneration of E. longifolia.